2018
DOI: 10.3390/molecules23092375
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Neurotransmitters Profiling Identifies Metabolic Signatures in Rat Brain by LC-MS/MS: Application in Insomnia, Depression and Alzheimer’s Disease

Abstract: Epidemiological, cross-sectional, and prospective studies have suggested that insomnia, Alzheimer’s disease (AD) and depression are mutually interacting conditions and frequently co-occur. The monoamine and amino acid neurotransmitter systems in central nervous system were involved in the examination of neurobiological processes of this symptom complex. However, few studies have reported systematic and contrastive discussion of different neurotransmitters (NTs) changing in these neurological diseases. Thus, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
2
34
0
3
Order By: Relevance
“…Finally, transdermal E2 improves sleep quality, reduces sleep latency, and decreases awakenings in postmenopausal women (47-65 years), especially those with insomnia ( 92 , 93 ). Given that sleep apnea/insomnia are risk factors for Alzheimer’s disease (AD) ( 94 , 95 ), attenuating risk at midlife can have important implications for women’s health. Thus, greater research attention paid to the potential role of E2/P in preventing sleep disorders at midlife is needed.…”
Section: Contributions Of Menopause-associated Hormone Changes To Slementioning
confidence: 99%
“…Finally, transdermal E2 improves sleep quality, reduces sleep latency, and decreases awakenings in postmenopausal women (47-65 years), especially those with insomnia ( 92 , 93 ). Given that sleep apnea/insomnia are risk factors for Alzheimer’s disease (AD) ( 94 , 95 ), attenuating risk at midlife can have important implications for women’s health. Thus, greater research attention paid to the potential role of E2/P in preventing sleep disorders at midlife is needed.…”
Section: Contributions Of Menopause-associated Hormone Changes To Slementioning
confidence: 99%
“…Interestingly, GR or PR inhibited D-gal-and Aβ 25-35 -triggered augmentation of AChE, whereas KXS further intensified this effect (Figure 2(g)). Previous studies showed that the concentration of ACh was significantly reduced in the AD model with HPLC-MS/MS quantitative analysis [31]. It was suggested that KXS could ameliorate ACh loss (correlated with cognition impairment of AD) by suppressing the activity of AChE.…”
Section: Resultsmentioning
confidence: 99%
“…Six groups of AD rats were administered intragastrically with KXS (10.0 g/kg), GR (3.0 g/kg), PR (2.0 g/kg), PO (3.0 g/kg), AT (2.0 g/kg), and Hup A (0.027 mg/kg) once a day from the third week until the end of the experiment [25]. At the end of the fourth week, the stereotaxic injection of 4 μg Aβ [25][26][27][28][29][30][31][32][33][34][35] (1 μg/μL) was operated at the following coordinates: anteroposterior-3.5; mediolateral-+2.0; and dorsoventral-2.8 mm [26]. Two weeks later, the Morris water maze test was used for evaluation.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Till date, studies conducted on the role of metabolites in diseases have mainly focused on the drugs and metabolic pathways (Li et al, 2011), the diseases and metabolic pathways (Li et al, 2012), or the metabolome in a single disease (Gonzalez et al, 2018;Xu et al, 2018;Che et al, 2019). The research on the relationship between diseases and metabolites is still limited, despite the fact that metabolic diseases have become highly frequent.…”
Section: Discussionmentioning
confidence: 99%